The significance of the concept "Ubuntu" for educational management and leadership during democratic transformation in South Africa - Msengana, Nontobeko Winnie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Education and Policy Studies))--University of Stellenbosch, 2006.